Shrinking Cities, villes en décroissance : une mesure du phénomène en France - Manuel Wolff (Unité Mixte de Recherche 8504 Géographie-cités, 2013)
While shrinking cities are the object of a growing interest in Europe and in the United States, they remain understudied in France. Indeed, few research works have been dedicated to the topic and urban policies, at least at the national level, do not deal with this question. This situation could find an explanation in the fact that the process of urban shrinkage, in France, has not reached the point where it could get academic and politic attention. In order to verify this hypothesis, this article aims at measuring the extent of the phenomenon of urban shrinkage in France. It will try to assess whether this process, although internationally recognized, is in France as marginal as the lack of interest it creates suggests or whether its evolution could lead to a better recognition by national policies.